Criminal Liability for Syahbandar's Negligence in Granting a Ship Permit That Resulted in an Accident - Ari Suganda; Fitri Rafianti; Henry Aspan (Judge : Jurnal Hukum, 2026)
Shipping safety is a fundamental principle in the maritime legal system that places Syahbandar as a key actor in ensuring the seaworthiness of ships through the granting of sailing permits. However, the practice of ship accidents that continue to occur even though the ship has obtained a Sailing Approval Letter shows that there are structural problems in the mechanism of supervision and accountability of authority, especially related to the negligence of office (culpa in officio). This study aims to analyze the legal basis for granting sailing permits, Syahbandar's role in law enforcement against unlicensed ships, and the construction of Syahbandar's criminal liability for negligence in granting ship permits that resulted in accidents. The research method used is normative juridical with a case approach, focusing on the tragedy of the sinking of KM Sinar Bangun in Lake Toba, through literature studies of laws and regulations, criminal law doctrines, scientific literature, and official documents. The results of the study show that the sailing permit is a preventive legal decision and not just an administrative formality, so that negligence in the issuance process has the potential to negate the shipping safety function. Syahbandar normatively has an active legal obligation in ensuring the seaworthiness of the ship, and such negligence can form a causal relationship with the occurrence of an accident. Although the Shipping Act does not explicitly regulate criminal sanctions, criminal liability is still possible through the application of general criminal law. This study concludes that Syahbandar's negligence in granting permits for ships that are not seaworthy can be qualified as a criminal offense that meets the elements of forgetfulness and deserves criminal responsibility in order to ensure accountability and public safety.